PEMBERDAYAAN DIFABEL PERSPEKTIF PEKERJA SOSIAL DI ROEMAH DIFABEL KOTA SEMARANG - Marwanti, Theresia Martina; Wibawa, Catur Hery; Brameswary, Hendrasty Candrika (Pekerjaan Sosial, 2024)
Empowering people with disabilities as a form of social work is rarely discussed from a social worker's perspective, giving rise to bias. Discussion of empowering people with disabilities is limited to certain segmentations and does not yet present the main goal of empowerment, namely social welfare. This study will further explore the empowerment of disabled people carried out by Roemah Difabel in Semarang City using the perspective of social workers. Data was collected using participant observation and semi-structured interviews. The results of the research show that Roemah Difabel in Semarang City has fulfilled the construction of the value of empowering disabled people for social welfare, namely in the form of restoring family life, helping overcome problems, increasing abilities, and facilitating access. Some of the empowerment activities carried out include education, skill improvement, advocacy, and ease of information dissemination. Meanwhile, there are several weaknesses in the empowerment of disabled people by Roemah Difabel. Some of these weaknesses are the lack of facilities to support the activity process at Roemah Difabel, the small number of volunteers compared to the number of disabled people who are members at Roemah Difabel, and the lack of human resources for volunteers to support activities at Roemah Difabel.